2005
DOI: 10.1111/j.1572-0241.2005.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Alterations and Clinical Features in Early-Onset Colorectal Carcinomas and Their Role for the Recognition of Hereditary Cancer Syndromes

Abstract: Our study demonstrates the involvement of CIN in a majority of early-onset colorectal tumors. Furthermore, we identified Lynch syndromes in seven cases (50%) of early-onset colorectal carcinomas with impairment of the MMR system. These results suggest that patients with early-onset CRC should be screened for hereditary cancer syndrome through clinical and molecular characterizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…Our results showed that the immunohistochemical analysis of MMR proteins and confirmation by using four monomorphic markers (BAT25, BAT26, NR21, and CAT25) revealed a rate of 15% instability (10/70 (18). Whatever the origin of this MSI, testing for MSI is important.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results showed that the immunohistochemical analysis of MMR proteins and confirmation by using four monomorphic markers (BAT25, BAT26, NR21, and CAT25) revealed a rate of 15% instability (10/70 (18). Whatever the origin of this MSI, testing for MSI is important.…”
Section: Discussionmentioning
confidence: 98%
“…The MSI status was evaluated using 4 mononucleotide markers (BAT25, BAT26, NR24 and CAT25) (13). Using this panel of monomorphic markers, a tumor was defined as MSI-positive when at least 2 markers showed instability.…”
Section: Microsatellites Analysismentioning
confidence: 99%
“…In comparison to elder CRC, EOCRC cases have some distinguishing clinical and pathological features [11,12] . These tumors are pathologically recognized with lowgrade tumor differentiation, mucinous component and high signet ring cells frequency [11,13] .…”
Section: Molecular Pathogenesis Of Eocrcmentioning
confidence: 99%
“…These tumors are pathologically recognized with lowgrade tumor differentiation, mucinous component and high signet ring cells frequency [11,13] . Polyp development is contently observed during the follow-up period of EOCRC [10] .…”
Section: Molecular Pathogenesis Of Eocrcmentioning
confidence: 99%
See 1 more Smart Citation